2018
DOI: 10.1029/2018jb015615
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and Dynamics of the Pamir, Central Asia: Quantifying the Roles of Continental Subduction in Force Balance

Abstract: An updated kinematic model constrained by GPS observations and fault slip rate information from the Central Asia Fault Database provides updated modeled slip rates for major faults in the Pamir. The kinematic model constrains thin sheet continuum mechanics models that distinguish the contributions of subducting continental lithosphere to force balance. Dynamic model sensitivity tests show that major features of the force balance results are insensitive to chosen lithospheric compensation style, integration dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
(193 reference statements)
1
5
0
Order By: Relevance
“…On the decadal timescale, GPS measurements have shown that present-day ~N-S shortening rates across the PTS range from 10 to 15 mm/yr (Zubovich et al, 2010;Ischuk et al, 2013;Zhou et al, 2016). The rates are consistent with the modeling rates (11.8-14.4 mm/yr) from a kinematic model based on recent GPS velocities and Quaternary fault slip rates (Jay et al, 2017;Jay et al, 2018). The velocities from four GPS stations across one strand of the western PFT indicated a shortening rate of 2.2 ± 0.8 mm/yr and dextral-slip rate of 5.6 ± 0.8 mm/yr near the Altyndara River (Zubovich et al, 2016).…”
Section: Pamir Thrust Systemsupporting
confidence: 75%
“…On the decadal timescale, GPS measurements have shown that present-day ~N-S shortening rates across the PTS range from 10 to 15 mm/yr (Zubovich et al, 2010;Ischuk et al, 2013;Zhou et al, 2016). The rates are consistent with the modeling rates (11.8-14.4 mm/yr) from a kinematic model based on recent GPS velocities and Quaternary fault slip rates (Jay et al, 2017;Jay et al, 2018). The velocities from four GPS stations across one strand of the western PFT indicated a shortening rate of 2.2 ± 0.8 mm/yr and dextral-slip rate of 5.6 ± 0.8 mm/yr near the Altyndara River (Zubovich et al, 2016).…”
Section: Pamir Thrust Systemsupporting
confidence: 75%
“…We next calculate the deviatoric stresses arising from those GPE variations by solving the depth integrated (from a variable surface elevation to a reference depth of 100 km below the sea level) force-balance equations on a global grid with lateral viscosity variations, using the "thin sheet" approximation (Ghosh et al, 2006(Ghosh et al, , 2009. Earlier studies have shown that integrating to depths shallower or deeper than 100 km does not substantially affect the GPE differences and hence the associated deviatoric stresses (Ghosh et al, 2009;Hirschberg et al, 2018;Jay et al, 2018;Klein et al, 2009). The second step involves calculating deviatoric stresses associated with horizontal tractions acting at a specific reference depth (base of depth integration, 100 km below sea level), which are obtained from a global mantle circulation model driven by tomography and history of subduction (Wen & Anderson, 1997), along with lateral viscosity variations in the lithosphere (Ghosh et al, 2008;Ghosh & Holt, 2012).…”
Section: Stresses Resulting From Topography and Large-scale Mantle Flowmentioning
confidence: 99%
“…() and Jay et al. (). In the east, the Sagaing fault shows E‐W compression whereas dominantly N‐S compression is seen in the Bengal fan.…”
Section: Resultsmentioning
confidence: 99%
“…For a common reference level, we assume a depth of 100 km below sea level, but this depth can be varied. Integrating up to different depths will change the total GPE, but not the GPE differences and hence the associated deviatoric stresses will remain largely unaffected (Ghosh et al., ; Hirschberg et al., ; Jay et al., ; Klein et al., ). We calculate GPE using CRUST1.0 model (Laske et al., ) that gives the thickness and densities of various crustal layers on a 1° × 1° global grid.…”
Section: Methodsmentioning
confidence: 99%